Assisted Per-Vaginal Delivery of Monocephalic Sternopagus Fetus in a Non-Descript Doe - Kumar, Mahesh; Singh, Avaneesh Kumar; Sachan , Vikas (The Indian Journal of Animal Reproduction, 2025)
The present communication is a report of assisted per-vaginal delivery of a rare conjoined twin male monster (Monocephalus Sternopagus Tetrabrachius Tetrapus Dicaudatus) fetus in a non-descript primiparous Doe.
Keywords: Doe; Dystocia; Monster; Monocephalus; Sternopagus